IMPROVING THE DELIVERY OF HIV OUTPATIENT SERVICES IN SUB-SAHARAN AFRICA. Issue 1 (1st March 2013) - Gordge, L; Selman, L; Harding, R; Higginson, I J; Simms, V; Penfold, S; Powell, R A; Mwangi-Powell, F; Dowing, J; Gikaara, N; Munene, G
Abstract : Introduction: The majority of care for the 22.9 million people with HIV in Sub-Saharan Africa is provided by HIV outpatient services. While the palliative care needs of HIV patients are well documented, it is not known how well HIV outpatient services meet these needs and evidence to improve service provision is lacking. Aims and Methods: To explore the care provided by outpatient HIV services in Uganda and Kenya and identify ways of improving care to meet patient and family needs. Qualitative interviews were conducted with patients, carers and staff at 12 HIV outpatient facilities (six in Kenya, six in Uganda), translated into English and analysed thematically. Results: 189 people were interviewed (83 patients, 47 caregivers, 59 staff). Positive aspects of care related to staff attributes and teamwork, holistic care, medication provision and patient education. Gaps/challenges in care related to service efficiency, paediatric services, reaching rural areas, poverty and sustaining services financially. Services struggled to meet patient demand through lack of staff, resources and space. Drug availability was variable, but when good was highly valued by service users. Recommendations included improving existing services (organisation, medication provision and staff training) and providing additional services and outreach (transport, public health initiatives, nutritional programmes, financial support and care for extended family). Conclusions: Outpatient services struggled to meet the multidimensional needs of people living with HIV in the face of significant resource challenges. Findings can be used to improve outpatient care and direct financial resources. Collaboration with palliative care services may help to improve HIV outpatient care.